Inherence of Indonesian Identity in The Foreign Language Point of View - Hiwakari, Joseph Matthew; Anjanette, Chanelle (JLA (Jurnal Lingua Applicata), 2025)
Indonesia is a country with a rich tapestry of culture. Each culture represents a group of people in a specific region, and each region speaks using their own native language. In order to preserve each local language, the role of international language is highly needed to make sure that people from other nations can communicate with locals and engage in local traditions respectfully. An utmost importance in this case is the use of international language. International travellers in most tourism sites in Indonesia, such as Bali, Yogyakarta, or Labuan Bajo, tend to speak using either English or Chinese language to interact with local sellers or accommodation workers. Other tourists, on the other hand, use Indonesian language in purchasing items from locals or simply for asking directions in order to gain new soft skills and have a better proximity among each other. This research paper is made with care in order to analyse how foreign language is inherent and important in order to shape each individual’s worldview and to conserve local cultures and traditions from extinction which would cause future generations to be able to experience them as well.